HARMONISASI PANCASILA DENGAN AGAMA DALAM PRESPEKTIF HUKUM ISLAM - Irwansyahlubis; M. Sidik; Muhammad Sibawaih (JURNAL CERDAS HUKUM, 2022)
The discourse on religion and Pancasila State is actually a classic theme, but it is still relevant as a topic for academic and theological studies. That's because of the variety of schools of thought that develop in seeing the correlation between religion and the state. The first school said that religion and the state are two different entities, so they cannot be equated. And other schools consider that religion is a complete teaching. His teachings have collected the values ​​of life, including the teachings of politics and the state. This school concludes that the concept of the State does not need to be confused with the concepts that already exist in religion. Paradigm differences in interpreting the correlation between religion and the state ultimately lead to wild and varied interpretations. So that the view of both of them raises various poles of views and different paradigms. Meanwhile, the results of this study show that it is undeniable that the two are indeed different entities. But in practice the two are an inseparable unit. Each other has affiliation and complements each other, especially for harmony in religious and state life. Even in Islamic law, there are no boundaries between religion and the state. In fact, Islamic law focuses on the love of the State. And the essence of Pancasila in its most fundamental principle has similarities with the Islamic religion. For this reason, religious leaders and other figures should participate in campaigning for love for the homeland, this can be done through the da'wah pulpit or other forums. Both using the Islamic perspective and with other perspectives.